2003
DOI: 10.1073/pnas.1633363100
|View full text |Cite
|
Sign up to set email alerts
|

A high-molecular-weight complex of membrane proteins BAP29/BAP31 is involved in the retention of membrane-bound IgD in the endoplasmic reticulum

Abstract: B cell antigen receptors (BCRs) are multimeric transmembrane protein complexes comprising membrane-bound immunoglobulins (mIgs) and Ig-␣͞Ig-␤ heterodimers. In most cases, transport of mIgs from the endoplasmic reticulum (ER) to the cell surface requires assembly with the Ig-␣͞Ig-␤ subunits. In addition to Ig-␣͞Ig-␤, mIg molecules also bind two ER-resident membrane proteins, BAP29 and BAP31, and the chaperone heavy chain binding protein (BiP). In this article, we show that neither Ig-␣͞Ig-␤ nor BAP29͞BAP31 nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 49 publications
6
68
0
2
Order By: Relevance
“…11 ), we observed some cleavage of BAP31 associated with mitochondria (results not shown). BAP31 is an abundant protein of ER and Golgi membranes 28 that facilitates the retention of proteins within early secretory organelles 29,30 and has been reported to be cleaved by caspase-8. 13 However, BAP31 cleavage was limited and did not extend to all membrane fractions, thereby reducing the possibility of its direct involvement in the traffic alteration observed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 ), we observed some cleavage of BAP31 associated with mitochondria (results not shown). BAP31 is an abundant protein of ER and Golgi membranes 28 that facilitates the retention of proteins within early secretory organelles 29,30 and has been reported to be cleaved by caspase-8. 13 However, BAP31 cleavage was limited and did not extend to all membrane fractions, thereby reducing the possibility of its direct involvement in the traffic alteration observed here.…”
Section: Resultsmentioning
confidence: 99%
“…35 For instance, Fas signalling may impact on secretory routes linking ER with proximal Golgi by early modification of BAP31 13 or similar traffic regulators that retain selected membrane proteins within the ER. 29 Functional alteration of these ER retention proteins via caspase cleavage could induce a dispersal and surface exposure of specific membrane proteins, 29,30 that may include glycoproteins reacting with HPA. 36 Our finding that inhibition of (predominantly) caspase-8 prevents early dispersal of Golgi membranes provides a novel dimension to the early action of apical caspases, especially in type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 These results indicate that accumulation of mutant ␣1ATZ in the ER results in activation of the caspase cascade via both the ER and mitochondrial pathways. For another, we found (unpublished observations) that accumulation of ␣1ATZ in the ER specifically mediated the cleavage/activation of BAP31, an integral membrane protein of the ER that is involved in the ER retention of several proteins 35 and appears to mediate pro-apoptotic signals from the ER to mitochondria. 36 This last result may provide a mechanistic explanation for the mitochondrial dysfunction that was recently found in cell line and transgenic mouse models of ␣1AT deficiency as well as in the liver of deficient patients.…”
Section: Cellular Response Pathways Activated By Er Retention Of ␣1atzmentioning
confidence: 94%
“…Bap31 and its homologue Bap29 were originally discovered as B cell receptor-associated proteins (Kim et al, 1994). Although solid evidence demonstrated that Bap31 is involved in apoptosis (Breckenridge et al, 2003), accumulating evidence suggest that Bap31 in healthy cells functions as a cargo receptor for ER export of transmembrane proteins, such as cellubrevin, class I major histocompatibility complex (MHC) molecules, CFTR, membrane-bound immunoglobulin (Ig)G, tetraspanins, cytochrome P450 2C2, and the leukocyte integrin CD11b/CD18, some of which are well-known ERAD substrates (Annaert et al, 1997;Spiliotis et al, 2000;Lambert et al, 2001;Schamel et al, 2003;Paquet et al, 2004;Zen et al, 2004;Stojanovic et al, 2005;Ladasky et al, 2006; SzczesnaSkorupa and Kemper, 2006).In the present study, we show that Bap31 is a component of the ER quality control compartment and that it cycles between the peripheral ER and a juxtanuclear ER or an ER-related compartment along microtubule tracks. …”
mentioning
confidence: 99%